The genetic tumor background is an important determinant for heterogeneous MYCN‐amplified neuroblastoma. Issue 1 (22nd March 2016) - Bogen, Dominik; Brunner, Clemens; Walder, Diana; Ziegler, Andrea; Abbasi, Reza; Ladenstein, Ruth L.; Noguera, Rosa; Martinsson, Tommy; Amann, Gabriele; Schilling, Freimut H.; Ussowicz, Marek; Benesch, Martin; et al.
Abstract : Amplification of MYCN is the signature genetic aberration of 20–25% of neuroblastoma and a stratifying marker associated with aggressive tumor behavior. The detection of heterogeneous MYCN amplification (hetMNA) poses a diagnostic dilemma due to the uncertainty of its relevance to tumor behavior. Here, we aimed to shed light on the genomic background which permits hetMNA in neuroblastoma and tied the occurrence to other stratifying markers and disease outcome. We performed SNP analysis using Affymetrix Cytoscan HD arrays on 63 samples including constitutional DNA, tumor, bone marrow and relapse samples of 26 patients with confirmed hetMNA by MYCN ‐FISH. Tumors of patients ≤18m were mostly aneuploid with numeric chromosomal aberrations (NCAs), presented a prominent MNA subclone and carried none or a few segmental chromosomal aberrations (SCAs). In older patients, tumors were mostly di‐ or tetraploid, contained a lower number of MNA cells and displayed a multitude of SCAs including concomitant 11q deletions. These patients often suffered disease progression, tumor dissemination and relapse. Restricted to aneuploid tumors, we detected chromosomes with uniparental di‐ or trisomy (UPD/UPT) in almost every sample. UPD11 was exclusive to tumors of younger patients whereas older patients featured UPD14. In this study, the MNA subclone appears to be constraint by the tumor environment and thus less relevant for tumor behavior in aggressive tumors with a high genomic instability and many segmental aberrations. A more benign tumor background and lower tumor stage may favor an outgrowth of the MNA clone but tumors generally responded better to treatment. Abstract : What's new? MYCN amplification (MNA) in neuroblastoma (NB) generally associates with an aggressive tumor behavior and detection of MNA leads to an automatic upstaging of the tumor in non‐stage 1 tumors. But what if only a fraction of the tumor cells is MYCN ‐amplified? To investigate the diagnostic importance of heterogeneous MNA, the authors conducted a genetic analysis of samples from 26 NB patients with a particular focus on accompanying genetic aberrations. They concluded that tumor behavior is largely dependent on patient age and other chromosomal alterations in the genetic tumor background rather than the mere presence of the MNA clone.